Investigating the Effect of Simulated Reference Frames on Spatial Orientation in Virtual Reality - Nguyen-Vo, Thinh; Riecke, Bernhard E.; Stuerzlinger, Wolfgang (Second International Workshop on Models and Representations in Spatial Cognition, 2017)
When navigating in virtual environments, users can easily and quickly get disoriented, especially when reliable landmarks are missing. Here, we investigate if a simple visually simulated reference frame helps users maintain their sense of direction in HMD-based virtual reality. Participants performed a navigational search task where they searched for eight hidden target objects in 16 boxes randomly positioned and rotated in a 5x5 meter circular area within a virtual environment otherwise devoid of landmarks. Participants wore an HTC Vive head-mounted display and were seated on a NaviChair motion cueing stool (Swopper stool mounted on a Wii force plate) that allowed them to control simulated front/back and sideways motions by leaning into the corresponding direction, and rotations by physically rotating. In a pre-study comparing the NaviChair motion cueing stool with a standard joystick interface, participants frequently experienced motion sickness with the joystick. Thus, we dropped this condition from consideration. In the main experiment, we compared three different reference frame conditions. The baseline featured no enhancements. In the “simulated CAVE” condition a wireframe rectangular box provided an egocentric reference frame that followed participants when moving, but stayed oriented in the same direction. The last condition featured an allocentric reference frame, i.e., a wireframe box acting as a “simulated room”, which was stationary regardless of participants’ navigation. The egocentric reference frame, i.e., the simulated CAVE, showed no benefits over the baseline condition. Yet, the allocentric reference frame, i.e. the simulated room, improved performance as indicated by shorter task completion times, reduced distances traveled, lower number of revisits, and higher subjective preference ratings. Although further research is needed, results suggest that providing a simple allocentric reference frame may be a simple, yet cost-effective way to improve the efficiency of locomotion in virtual environments without landmarks.
Keywords: Riecke; Riecke_2017; bernhard-riecke; iat802; iat802_fall2016; leaning-based interfaces; motion-cueing; naviChair; poster; posterWithoutPaper; proj--motionCueingInterfaces; proj--naviSearchInVR; talkWithoutPaper; thinh-nguyen-vo; wolfgang-stuerzlinger